Partisipasi Masyarakat dalam Pembentukan Undang-Undang Daerah Otonomi Baru Papua Perspektif Siyasah Dusturiyah - Yahya. S, Muhammad (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The purpose of this research is to find out whether the public participates in the formation of the New Autonomous Region Law in Papua and whether the formation of the New Autonomous Region Law in Papua complies with the legislative process and principles of law formation in Islam. The research uses library research method with a normative juridical approach. The results show that the formation of the New Autonomous Region in Papua has not involved the participation of the Papua community in formulating and drafting the Papua NAR Law, and that the formation of the Papua NAR Law from a siyasah dusturiyah perspective does not meet the principles of consultation, freedom of expression, and jalb al-masalih wa dar al-mafasid (taking good and rejecting evil).